Lifetime Prediction of Pan Feeder Based on 3D Laser Scanning for Wear Assessment - Maulidya, Nony; Priadi, Dedi; Asral, D. Rizal (UI Scholars Hub, 2024)
Apron feeder is one of stages in crushing circuit to convey material in short distance. Pan flight is the main component of apron feeder that is severely exposed to wear mechanism due to its direct contact with open cut abrasive ore. With this operating environment of apron feeder, regular maintenance and inspection must be conducted to assess wear rate of pan’s surface to maintain equipment availability and provide information and sign before the equipment undergoes severe and sudden degradation. 3D laser scanning is method used in this study as Non-Destructive Testing (NDT) based inspection. The aim of using 3D scanning is to model the actual condition of pan and give measurement of wear. Later this scanning data is analyzed for forecasting life prediction of when pan surface reaches its safe minimum thickness. Utilizing 3D scanning for wear measurement offers comprehensive analysis, precise measurements with visualization capabilities and handling geometries effectively. Life prediction derived from this analysis can be used as decision making to determine next replacement date of pan feeder using regression model and linear calculation. Results after four times conducting this inspection with four months period consistently, showing that the safe replacement time will be on the earliest second trimester of 2024. This provides an advantage on the shutdown planning side to prepare resources and timetable early and effectively.